Concept Analysis: Wrong‐Site Surgery. (28th May 2015) - Watson, Donna S.
Abstract: A concept analysis was conducted on the concept of wrong‐site surgery (WSS) using the principle‐based method by Penrod and Hupcey. It included analysis of WSS within the context of epistemological, pragmatic, linguistic, and logical principles. The analysis found that WSS is an important concept that is universally accepted, but the definition could be improved with inclusion of comprehensive labeling for types of WSS that may occur, such as wrong patient, wrong site, wrong level/part, wrong procedure, and wrong side. Wrong‐site surgery falls into the domains of both nursing and medicine, and there is limited research on the topic specific to nursing interventions, perceptions, and contributions to prevent WSS.